2015
DOI: 10.1016/j.jviromet.2015.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of vesicular stomatitis virus populations by tunable resistive pulse sensing

Abstract: Although transmission electron microscopy (TEM) has historically been the method of choice to estimate concentrations of virus and virus-like particles, these measures can often be time-consuming and labor-intensive to perform. Tunable resistive pulse sensing (TRPS) is an emerging method that applies principles of Coulter counting to nanoscale particles and may provide a simpler and higher-throughput alternative to TEM for the quantitation of virus populations. To assess the performance of TRPS compared to TEM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 23 publications
0
34
0
Order By: Relevance
“…The DIP-GFP working stock was prepared by infecting BHK cells transfected with pMD2.G. The particle concentrations of the DIP and DIP-GFP stocks were determined via tunable resistive pulse sensing [ 60 , 61 ]. The concentration determined by these particle counts were similar to those determined by qPCR [ 56 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DIP-GFP working stock was prepared by infecting BHK cells transfected with pMD2.G. The particle concentrations of the DIP and DIP-GFP stocks were determined via tunable resistive pulse sensing [ 60 , 61 ]. The concentration determined by these particle counts were similar to those determined by qPCR [ 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…At 24 hpi the cells were imaged on a Nikon TE Eclipse 300 inverted microscope, and the supernatant was collected and stored at -80°C. The number of infectious virus particles in the supernatant was determined by plaque assay, and the total particle counts, which includes infectious and non-infectious particles, were determined using tunable resistive pulse sensing via a qViro (IZON Science, Christchurch, NZ) [ 60 ].…”
Section: Methodsmentioning
confidence: 99%
“…Farkas and coworkers counted rotavirus (75 nm) using both qRT-PCR and qNano to evaluate the purification of the viruses by size-exclusion chromatography (Farkas et al, 2013 ). Akpinar and Yin counted vesicular stomatitis virus (70 × 200 nm) using both TRPS and a plaque assay (Akpinar and Yin, 2015 ). The average total to infectious particle ratio was calculated as 2.91 ± 1.42.…”
Section: Applications Of Rps For Virus Detectionmentioning
confidence: 99%
“…They were able to measure the size and density of human immunodeficiency virus and Epstein-Barr virus. Using vesicular stomatitis virus (VSV) and 100nm polymer spheres as size controls, Akpinar & Yin [75] has shown that TRPS was able to quantify concentrations down to 107 particles per ml which was 50 fold lower than the detection limit of TEM. TRPS produced more reproducible counts than TEM.…”
Section: The Role Of Trps In Microbiologymentioning
confidence: 99%